2023
DOI: 10.1021/acs.energyfuels.3c00899
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of Transitional Shale and Evolution of Physical Properties Constrained by Concurrent NMR and Acoustic Observations

Abstract: Hydration state is a key factor affecting the pore structure and mechanical properties of shale that directly impacts the migration and then production of geofluids. We quantify the impact of the hydration state on physical properties through spontaneous imbibition experiments constrained by concurrent nuclear magnetic resonance (NMR) and acoustic observations as diagnostics of response. The long-duration experiments (24 days) are on samples from the Permian Shanxi Formation of the Ordos Basin, complemented by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The samples were collected from wells LX2–48 (sample V1) and LX-152 (sample V2), part of the Carboniferous-Permian Taiyuan Formation. The Taiyuan Formation is mainly barrier islands, tidal flats, and lagoon sedimentary environments . This formation is composed of a set of interbedded sediments including coal seams, shales, and tight sandstones. , The burial depths of the collected samples are1998.18 and 1761.30 m, and the shale in the study area is transitioning within the mature to postmature hydrocarbon generation stage .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were collected from wells LX2–48 (sample V1) and LX-152 (sample V2), part of the Carboniferous-Permian Taiyuan Formation. The Taiyuan Formation is mainly barrier islands, tidal flats, and lagoon sedimentary environments . This formation is composed of a set of interbedded sediments including coal seams, shales, and tight sandstones. , The burial depths of the collected samples are1998.18 and 1761.30 m, and the shale in the study area is transitioning within the mature to postmature hydrocarbon generation stage .…”
Section: Methodsmentioning
confidence: 99%
“…(a) Location of the Ordos Basin in the North China Craton (modified with permission from ref . Copyright 2018 Springer Nature); (b) tectonic divisions of the Ordos Basin (modified from ref . Copyright 2023 American Chemical Society); (c) lithologic section and depositional environment in the Linxing area.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the studies for core experiments mainly focus on the comparison of self-absorption and backdriving, determination of mechanical properties, exploration of microstructure, and proppant reflux law. For example, Duan (2021) proposed a new diffusion model through the dual means of modeling and experimentation to achieve quantitative calculation of shale gas diffusion flow under given reservoir conditions, which meets the needs of engineering to accurately adjust the production system . Chen (2018) demonstrated that gypsum crystallization during shale–fluid reaction can induce fracturing to increase production by means of chemical experiments, and found that mineral crystallization or growth-induced spontaneous microfracture extension effect .…”
Section: Introductionmentioning
confidence: 99%